2020
DOI: 10.1111/dmcn.14665
|View full text |Cite
|
Sign up to set email alerts
|

Assessing communicative participation in preschool children with the Focus on the Outcomes of Communication Under Six: a scoping review

Abstract: Aim To describe uses of the Focus on the Outcomes of Communication Under Six (FOCUS) in research with children with and without various communication disorders since its publication in 2010. Method Six databases were searched for the term ‘Focus on the Outcomes of Communication Under Six’. With additional searches we ascertained 70 articles, of which 25 met inclusion criteria for full review and data extraction. Results The FOCUS has been used in research across multiple countries, purposes, populations, conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In concert with the emerging construct validity evidence, this is one of the first studies to attempt to validate the FOCUS Profile scores (cf. Cunningham et al, 2020). In the present case, in relation to preschoolers’ functional language use and expressive language skills as such, these findings fulfill calls to investigate the validity evidence for the use of the FOCUS Profile scores and also contribute to what is known about the relationship between children’s communicative participation and their speech and language abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In concert with the emerging construct validity evidence, this is one of the first studies to attempt to validate the FOCUS Profile scores (cf. Cunningham et al, 2020). In the present case, in relation to preschoolers’ functional language use and expressive language skills as such, these findings fulfill calls to investigate the validity evidence for the use of the FOCUS Profile scores and also contribute to what is known about the relationship between children’s communicative participation and their speech and language abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study provides preliminary validity evidence for the use of the FOCUS Profile scores (cf. Cunningham et al, 2020); offering a broader understanding about the relationship between speech and language abilities and communicative participation and further extending the psychometric evidence of the FOCUS measure. The identified associations between communicative participation and pragmatic skills may contribute to our understanding about the relevance of different pragmatic abilities across various multilingual/cultural populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper will also have implications for test developers who will want to understand a new standard for evaluating outcome measures. This work involves the secondary analysis of the data collected during a recent scoping review of the literature related to the FOCUS (Cunningham et al 2020). More specifically, we used the findings from this review to identify studies that reported psychomet-ric properties of the FOCUS, which we appraised using the COSMIN tools.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we used the findings from this review to identify studies that reported psychomet-ric properties of the FOCUS, which we appraised using the COSMIN tools. Cunningham et al (2020) identified 25 publications that reported on either the development or the application of the FOCUS. In the current study, we reviewed these 25 publications to identify those that reported psychometric properties of the FOCUS using the following inclusion criteria: (1) the article was peer reviewed and about the English-language version of the FOCUS or its derivative (i.e., the FOCUS-34); (2) the study evaluated the psychometric properties of the FO-CUS; and (3) the article was published in English.…”
Section: Introductionmentioning
confidence: 99%